Carbon Nanosheets Decorated Activated Carbon Derived from Borassus Flabellifer Fruit Skin for High Performance Supercapacitors. Issue 14 (19th October 2020) - Potphode, Darshna; Saha, Shalakha; Sharma, Chandra S.
Abstract : Here, we present an ingenious approach to convert bio-waste into porous carbon to fabricate a working electrode for the development of sustainable energy storage devices. Carbonization of Borassus Flabellifer fruit skin ( BFFS ) in an inert atmosphere was followed by KOH activation to synthesize partially graphitic carbon nanosheets attached to the porous carbon. Surface chemistry and porosity were tuned by varying the carbonization and activation temperature to achieve excellent control of the studied physiochemical properties. The as-obtained ABFFS -derived porous carbon exhibited a specific surface area of 1750 m 2 g −1 with distinctive morphology, showing great prospects for energy storage. The unique content of minerals in BFFS led to a highly porous architecture with a substantial volume fraction having micro- and meso-porosity. Symmetric supercapacitors were fabricated with 1 M H2 SO4 and EmimBF4 (ionic liquid) as electrolytes, and the specific capacitance reached values of 202 and 208 F g −1, respectively. The cycling stability of up to 94% at a current density of 2 A g −1 established a fairly stable performance for the supercapacitors based on biomass-derived carbon electrodes, and therefore, confirms the potential of BFFS -derived activated carbon for the advancement of supercapacitors based on bio-waste electrodes.